2009
DOI: 10.1007/s00167-009-0886-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of gait and muscle activation in chronic ACL deficiency

Abstract: The purpose was to investigate whether deviations in gait parameters or muscular activity patterns can be detected in the injured and healthy leg of chronic ACL-deficient subjects. Sixteen medium-level active chronic ACL-deficient patients classified as "copers" (injury duration: 12-240 months, age 17-52 years) and 15 healthy subjects (age 20-33 years) walked at self-selected speed along a 10-m runway with a level force-plate. Gait specific data, ground reaction forces, knee and ankle angles, and EMG were docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…Nevertheless, the delayed muscle activation onset times of the knee muscles in the acute phase after ACL injury are in line with the findings of Wojtys and Huston (1994). Other studies measuring muscle activation onset times after ACL injury mainly included chronic ACLI subjects (>6 months after injury) and reported mixed results (Beard et al, 1993;Bryant et al, 2009;Kalund et al, 1990;Lindstrom et al, 2009;Sinkjaer & Arendt-Nielsen, 1991). A previous study using the same experimental task in subjects with chronic ankle instability also reported delayed muscle activation onset times not only around the injured joint, but the absolute values of the delays cannot be compared, as the speed of movement was not standardized and the Mx onset was defined differently in their study (Van Deun et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, the delayed muscle activation onset times of the knee muscles in the acute phase after ACL injury are in line with the findings of Wojtys and Huston (1994). Other studies measuring muscle activation onset times after ACL injury mainly included chronic ACLI subjects (>6 months after injury) and reported mixed results (Beard et al, 1993;Bryant et al, 2009;Kalund et al, 1990;Lindstrom et al, 2009;Sinkjaer & Arendt-Nielsen, 1991). A previous study using the same experimental task in subjects with chronic ankle instability also reported delayed muscle activation onset times not only around the injured joint, but the absolute values of the delays cannot be compared, as the speed of movement was not standardized and the Mx onset was defined differently in their study (Van Deun et al, 2007).…”
Section: Discussionsupporting
confidence: 77%
“…The majority of previous studies assessing muscle activation patterns after ACL injury mainly focused on muscles surrounding the injured knee joint (Aalbersberg et al, 2009;Beard et al, 1993;Boerboom et al, 2001;Branch et al, 1989;Bryant et al, 2009;Ciccotti et al, 1994;Gauffin & Tropp, 1992;Houck et al, 2007;Kalund et al, 1990;Klyne et al, 2012;Lindstrom et al, 2009;Sinkjaer & Arendt-Nielsen, 1991;Swanik et al, 1999Swanik et al, , 2004Wojtys & Huston, 1994). The current study is the first to evaluate muscle activation onset times of the knee, hip and ankle after ACL injury during a standardized functional task, the transition from DLS to SLS.…”
Section: Discussionmentioning
confidence: 87%
“…Certainly, Kvist and Gillquist (2001) documented gastrocnemius and quadriceps co-contraction during various weight bearing tasks and concluded that such strategies could assist knee stability by virtue of joint compression. More recently, similar co-contraction strategies have also been observed in the lateral gastrocnemius and tibialis anterior muscles in ACLD individuals during level walking (Lindstrom et al, 2010).…”
Section: Discussionmentioning
confidence: 82%
“…In a similar task however, ACLD subjects elicited earlier activation of gastrocnemius to coincide with heel strike without concurrent increases in total muscle activity (Kuster et al, 1995). Comparable findings have recently been observed during level walking (Lindstrom et al, 2010). Finally, increased levels of medial gastrocnemius (MG) preparatory activity have been recorded in healthy subjects with ACL ligaments of above average laxity (>7 mm) prior to perturbation (Shultz et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation